2001
DOI: 10.1038/sj.bjp.0704131
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of cardiac and renal fibrosis by pirfenidone and spironolactone in streptozotocin‐diabetic rats

Abstract: 1 Fibrosis leads to chronic impairment of cardiac and renal function and thus reversal of existing ®brosis may improve function and survival. This project has determined whether pirfenidone, a new anti®brotic compound, and spironolactone, an aldosterone antagonist, reverse both deposition of the major extracellular matrix proteins, collagen and ®bronectin, and functional changes in the streptozotocin(STZ)-diabetic rat. 2 Streptozotocin (65 mg kg 71 i.v.)-treated rats given pirfenidone (5-methyl-1-phenyl-2-[1H]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(154 citation statements)
references
References 28 publications
9
144
0
1
Order By: Relevance
“…In agreement with previous reports on diabetic cardiomyopathy in STZ-induced diabetes [16,17], sham-operated diabetic rats in our study had larger LVEDD and higher relative heart weight than non-diabetic controls. However, sustained myocyte apoptosis in diabetic rats was observed only after they had been subjected to MI.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with previous reports on diabetic cardiomyopathy in STZ-induced diabetes [16,17], sham-operated diabetic rats in our study had larger LVEDD and higher relative heart weight than non-diabetic controls. However, sustained myocyte apoptosis in diabetic rats was observed only after they had been subjected to MI.…”
Section: Discussionsupporting
confidence: 94%
“…in rats increases blood glucose concentration. After 4 or 8 weeks of streptozotocin administration, animals showed collagen deposition in the kidneys, elevated renal plasma fibronectin concentrations (58) and elevated plasma levels of TGFβ, up to four times the normal levels (14). This model can be considered as a renal fibrosis model because sometimes, after the onset of diabetes, renal fibrosis may occur (58).…”
Section: Mercuric Chloride (Hgcl 2 )mentioning
confidence: 99%
“…Although not currently FDA approved, pirfenidone is licensed in Japan for the treatment of idiopathic pulmonary fibrosis, and animal models have indicated that pirfenidone can reverse fibrosis in the lungs, kidneys, and other organs. 60 In a pilot study of SIV-infected rhesus macaques, Dr. Schacker and his collaborators determined that pirfenidone had a protective effect on CD4 T cell populations in lymph nodes. A second pilot study looked at the effect of pirfenidone in combination with antiretroviral therapy.…”
Section: Treatment Of Lymphoid Fibrosis In Hiv/siv Infectionmentioning
confidence: 99%